Optimalisasi Kegiatan Promosi Desa Pace Sebagai Sentra Herbal - Eliyatiningsih, Eliyatiningsih; Erdiansyah, Iqbal; Sari, Vega Kartika; Nurahmanto, Dwi (Universitas Negeri Gorontalo, 2023)
Pace Village, Silo District is a center for herbal plant production with several main herbal commodities such as Ginger, Curcuma, Citronella, and Javanese chili. The community still does not know the potential of the village as an herbal center because the promotional activities are not yet intensive. This community service activity aims to improve partners' skills in carrying out promotional activities. This community service activity method is Participatory Rural Appraisal (PRA) approach with several activities including the coordination with partners, the counseling and promotion skills training, the mentoring, and the evaluation. In this community service activity partners are assisted in making promotional media, assisting exhibition activities, launching herbal product outlets, and creating a website. The results of the activity show that partners' understanding of promotional activities has increased, and promotional activities have had a significant impact on increasing partners' income in selling various herbal products.